Parental depression and emotional feeding practices are associated with a tendency towards overeating in preadolescents - Sarkkola, Catharina; Leppänen, Marja H.; Eloranta, Aino-Maija; Räisänen, Laura; Männistö, Satu; Viljakainen, Heli (Frontiers in Nutrition, 2025)
BackgroundChildren’s eating behaviors, including a tendency towards overeating, are strongly influenced by the family. Children prone to overeating are at a high risk of excessive weight gain, which can lead to further adverse health outcomes. Therefore, identifying factors that contribute to overeating is crucial for promoting healthy weight development. Given the inconsistencies in previous research, mostly involving young children, we investigated the child and parental characteristics associated with overeating in preadolescence.MethodsThe cross-sectional study included 5,973 preadolescents aged 9–12 years from the Finnish Health in Teens (Fin-HIT) cohort. A tendency towards overeating was based on a parent-reported question. We utilized extensive parent questionnaire and Medical Birth Register data, and used ordinal and stepwise logistic regression to identify the independent determinants of overeating.ResultsThe proportion of preadolescents with a parent-reported tendency towards overeating was 10% (n = 606). In the multivariable model, boys had higher odds of overeating (OR 1.30, 95% CI 1.06–1.58) compared with girls. Preadolescents with overweight and obesity had 9- and 30-fold odds (95% CI 7.31–11.29 and 20.07–44.54, respectively) of overeating compared with healthy-weight preadolescents. Furthermore, parental depression and emotional feeding increased the odds of overeating in the preadolescent (OR 1.48, 95% CI 1.08–2.02 and OR 1.27, 95% CI 1.03–1.57).ConclusionAlong with child weight status and sex, parental depression and emotional feeding were independently associated with overeating in preadolescence. Therefore, it is important to support parents’ mental health and their healthy feeding practices. Our findings can be targeted to manage overeating and prevent overweight in children and adolescents.